Adult education and the nation-state: A systematic review of literature - Hye-Su Kuk (Adult Education Research Conference, 2020)
In this literature review, I analyze how the concept of the state is defined and used in empirical adult education research articles. Findings are in three themes of 1) systems of governance in adult education, 2) governmentality and contention, and 3) research challenging whether the state boundaries are blurred in the adult education literature. I discuss the implications of the findings in comparison to theoretical approaches toward the state in adult education.
Keywords: state theory; literature review; system; governance; governmentality; globalization